The Role of Semantic in Daily Conversation: How Words Construct and Convey Meaning - Risma Novalina Sagala; Bernieke Anggita Ristia d (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to explore the role of semantics in constructing and conveying meaning in daily conversations. Using a literature review method, data were collected from primary sources such as linguistic textbooks and secondary sources including recent journal articles focusing on semantics, pragmatics, and digital communication. Findings show that semantic elements like word choice, connotation, denotation, and semantic fields interact with pragmatic aspects such as tone, pauses, and non-verbal cues to shape fluid, context-dependent communication. The analysis highlights that meaning is co-constructed between speakers and listeners, influenced by speaker intentions, listener background knowledge, cultural norms, and situational context. Overall, the study concludes that understanding semantics is essential for reducing misunderstandings and fostering more effective communication across various contexts.